ROLA RAD MŁODZIEŻOWYCH W LOKALNYM ŻYCIU PUBLICZNYM: WYNIKI BADAŃ EMPIRYCZNYCH - Boratyn, Dominik (Polityka i Społeczeństwo, 2020)
Youth councils are one of the entities functioning within local government units. According to law, the councils have an advisory character, but in practice these bodies also perform a number of other functions. Youth councils are forums that represent the views of young people at a local level; the councils shape, develop, activate, and educate the youth as well as create a forum for cooperation between local authorities and young people. The work in a youth council contributes to the development of a person's personality; it provides satisfaction, self-fulfillment; helps to develop social competences and to meet the need to be noticed and appreciated. The paper presents the results of empirical research, in which the author proves that the main role of youth councils is to activate the local life of young people.